2014
DOI: 10.1080/03057267.2014.957558
|View full text |Cite
|
Sign up to set email alerts
|

Equity in informal science education: developing an access and equity framework for science museums and science centres

Abstract: Informal science education (ISE) is a popular pursuit, with millions of people visiting science museums, science centres, zoos, botanic gardens, aquaria, science festivals and more around the world. Questions remain, however, about how accessible and inclusive ISE practices are. This article reviews research on participation in ISE through the lens of social inclusion and equity and suggests that, as a field of practice, ISE is exclusive, with relatively little empirical or theoretical research on equity compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
115
0
7

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 123 publications
(134 citation statements)
references
References 100 publications
5
115
0
7
Order By: Relevance
“…Research also suggests that capital can generate (more) capital. For instance, studies conducted within the field of informal science learning have found that museum visitors with higher levels of cultural capital can use this capital to leverage further capital and science learning from their visits (e.g., Archer, Dawson, Seakins, & Wong, in press, ; Dawson, , b).…”
Section: Bourdieu's Theorization Of Capitalmentioning
confidence: 99%
“…Research also suggests that capital can generate (more) capital. For instance, studies conducted within the field of informal science learning have found that museum visitors with higher levels of cultural capital can use this capital to leverage further capital and science learning from their visits (e.g., Archer, Dawson, Seakins, & Wong, in press, ; Dawson, , b).…”
Section: Bourdieu's Theorization Of Capitalmentioning
confidence: 99%
“…That controlling for these kinds of activities and learning opportunities does not reduce the gap‐in‐gaps for these groups, suggests that the gap‐in‐gaps may not be driven by differences in access to such early science learning opportunities but perhaps differences in the ways in which these venues engage with early learners from different linguistic or cultural backgrounds. For example, while disparities in access to science museums have been documented (Dawson, , ; Feinstein, ), prior work has drawn attention to the fact that even when access to such resources is available, cultural discontinuities as well as explicit and implicit bias and racism may impact the degree to which students benefit from such access (Dawson, , ; Feinstein, ). Feinstein () notes, “neither museum science nor school science is equally welcoming to everyone.…”
Section: Discussionmentioning
confidence: 99%
“…Efforts to diversify ISE participation that focus exclusively on providing greater access, inadvertently locate the “problem” within underserved communities. These efforts aim to help communities overcome limitations in their ability to access, navigate, and/or appreciate traditional ISE practices, reflecting deficit‐based, assimilationist, and/or colonialist perspectives (Bell et al., ; CAISE, ; Dawson, ; Garibay et al., ; Philip & Azevedo, ). In contrast, equity‐focused efforts locate the “problem” within ISE institutions and aim to reconceptualize ISE to reflect a broader range of cultures and practices (CAISE, ; Dawson, ; Garibay et al., ).…”
Section: Equity and Informal Stem Educationmentioning
confidence: 99%
“…These efforts aim to help communities overcome limitations in their ability to access, navigate, and/or appreciate traditional ISE practices, reflecting deficit‐based, assimilationist, and/or colonialist perspectives (Bell et al., ; CAISE, ; Dawson, ; Garibay et al., ; Philip & Azevedo, ). In contrast, equity‐focused efforts locate the “problem” within ISE institutions and aim to reconceptualize ISE to reflect a broader range of cultures and practices (CAISE, ; Dawson, ; Garibay et al., ). Consistent with literature in the field of organizational change, we refer to these actions as inclusive practices (e.g., Sabharwal, ).…”
Section: Equity and Informal Stem Educationmentioning
confidence: 99%